Breeding cowpea (Vigna unguiculata (L.) walp.) for improved drought tolerance in Mozambique - Chiulele, Rogério Marcos. (2012)
Cowpea yields in Mozambique can be increased through breeding farmers’ accepted cultivars with drought tolerance and stability across environments. A study was conducted in the southern region of Mozambique to: (1) determine farmers perceptions on major constraints limiting cowpea production and identify preferences regarding cultivars and traits, (2) determine the variability of selected cowpea germplasm for drought tolerance, (3) determine the gene action controlling drought tolerance, yield and yield components in cowpea, and (4) assess the genotype × environment interaction and yield stability of cowpea genotypes under drought-stressed and non-stressed conditions. The study on farmers’ perceptions about the major constraints limiting cowpea production and preferences regarding cowpea cultivars and traits established that cowpea was an important crop, cultivated for its grain, leaves and fresh pods for household consumption and the market. The study revealed that cowpea grain and leaves were equally important across the three districts in the study. Differences in accessibility to markets between districts influenced the ranking of grain and leaves among districts. Grain was more important in Bilene and Chibuto districts which are situated far from the major urban centre, Maputo, while leaves were more important in Boane district which is near the major market of Maputo. Fresh pods were important in Bilene district which is situated along the major highway connecting Maputo and other provinces. Drought was the most important production constraint followed by aphids, bruchids and viral diseases. The criteria used by farmers to select cowpea varieties included high grain and leaf yield, large seed size, earliness, smoothness of the testa and potential marketability of the variety. The implication of this study is that different types of varieties need to be developed for different areas. Dual-purpose or grain-type varieties need to be developed for areas situated far away from the major markets while varieties for leaf production need to be bred for areas near major markets. During the breeding process, a selection index needs to be adopted whereby drought tolerance, high grain and leaf yield, large seed size, smooth testa, earliness, aphids and bruchids resistance should be integrated as components of the index. High grain yield should receive high weight for varieties developed for areas located far from major markets while high leaf yield would receive high weight for varieties developed for areas located near major markets. The study on variability of cowpea germplasm collections for drought tolerance revealed wide genotypic variability among the tested germplasm. Biplot displays indicated that the genotypes could be grouped into four categories according to their drought tolerance and yielding ability as indicated below: high yielding-drought tolerant (group A), high yielding-drought susceptible (group B), low yielding-drought tolerant (group C), and low yielding-drought susceptible (group D). Examples of high yielding-drought tolerant genotypes were Sh-50, UC-524B, INIA-24, INIA-120, IT96D-610 and Tete-2. Stress tolerance index was the best criterion for assessing genotypes for variability in drought tolerance because it enabled the identification of high yielding and drought tolerant genotypes (group A). The assessment on gene action controlling drought tolerance (stay-green), yield and components indicated that both additive and non-additive effects were involved in controlling all of these traits. Additive gene action was more important than non-additive gene affects in controlling stay-green, days to flowering, number of pods per plant, number of seeds per pod and hundred seed weight. Under no-stress conditions, additive gene action was more important than non-additive gene action while under drought-stressed conditions, non-additive gene effects were more important than additive gene effects. Stay-green can easily be assessed visually in early segregating populations while yield and yield related traits cannot. Hence, selection for drought tolerance using the stay-green trait would be effective in early segregating generations while selection for yield and number of pods per plant would be effective in late segregating generations. Selection for yield could be conducted directly under no-stress conditions and indirectly using the number of pods per plant under drought stress conditions. Genotype INIA-41 would be the most desirable to use as a parent for drought tolerance and IT93K-503-1 would be the most desirable to use as a parent for drought tolerance and yield. The assessment on genotype × environment interaction and cowpea grain yield stability for forty-eight (48) cowpea genotypes grown under drought-stressed and non-stressed conditions indicated that cross-over genotype × environment interactions were present for yield indicating that genotypes responded differently to varying environmental conditions. Genotypes adapted to specific environmental conditions could be identified. Genotypes IT-18, INIA-51, INIA-51A and Nhavanca were adapted to non-stressed environments that were either drought stressed or non-stressed while VAR-11D was adapted to low yielding, stressful environments. Genotypes INIA-23A, INIA-81D, INIA-24, INIA-25, INIA-16 and INIA-76 were high yielding and stable while genotypes IT-18, INIA-51, INIA-51A, Nhavanca and VAR-11D were high yielding and unstable. Genotypes Bambey-21, INIA-36, INIA-12 and Monteiro were consistently low yielding and stable except INIA-12 that was consistently unstable. Chókwè was a high yielding environment and suitable for identifying high yielding genotypes but not ideal for selection because it was not representative of an average environment while Umbeluzi was low yielding and not ideal for selection. Overall, the study revealed that genetic improvement of drought tolerance and yield would be feasible. Potential parents for genetic improvement for yield and drought tolerance were identified. However, further studies for assessing yield stability of cowpea genotypes are necessary and could be achieved by including more seasons and sites to get a better understanding of the genotype × environment interaction and yield stability of cowpea in Mozambique. === Thesis (Ph.D.)-University of KwaZulu-Natal, Pietermaritzburg, 2010.